Clinical evidence of sesame (Sesamum indicum L.) products and its bioactive compounds on anthropometric measures, blood pressure, glycemic control, inflammatory biomarkers, lipid profile, and oxidative stress parameters in humans: a GRADE-assessed systematic review and dose–response meta-analysis - Ali Jafari; Bahare Parsi Nezhad; Niloufar Rasaei; Elahe Aleebrahim-Dehkordi; Abdolhalim Rajabi; Alireza Alaghi (Nutrition & Metabolism)
Abstract This comprehensive systematic review and meta-analysis aimed to assess the impact of sesame (Sesamum indicum L.) supplementation on cardiovascular disease risk factors. Relevant research was discovered via PubMed, Scopus, Web of Science, CENTRAL, and EMBASE up to June 2024. The assessment of study quality was conducted using the Cochrane risk-of-bias tool. Thirteen trials, with interventions ranging from 4 to 12 weeks and involving 521 participants, demonstrated significant reductions in glycated hemoglobin (HbA1c) (Standardized Mean Difference [SMD] = − 0.67; 95% Confidence Interval [CI] − 1.01, − 0.32; P < 0.001), C-reactive protein (CRP) (SMD = − 0.51; 95% CI − 0.96, − 0.05; P = 0.028), and interleukin-6 (IL-6) (SMD = − 0.74; 95% CI − 1.16, − 0.32; P < 0.001), and a marginally significant effect on fasting blood sugar (FBS) (SMD = − 0.57; 95% CI − 1.16, 0.02; P = 0.057). Subgroup analyses revealed that sesame supplementation significantly reduced CRP and malondialdehyde (MDA) in populations without chronic diseases, while total cholesterol (TC) and MDA were reduced in those with chronic diseases. MDA was significantly reduced in females, especially those aged 50 or older. At dosages of 10 g per day or less, CRP, high-density lipoprotein cholesterol (HDL), and TC showed significant improvements. Meta-regression highlighted a significant dose-dependent reduction in TC levels at 10 g/day, and a significant duration-dependent decrease in TG levels at 8 weeks of supplementation. Sesame supplementation demonstrates potential benefits in improving glycemic control, inflammatory markers, and lipid profiles, making it a promising adjunct therapy for reducing cardiovascular disease risk factors. Graphical abstract